Examining the Correlation and Predictive Power of Metacognitive Domains on Mathematics Performance Among Senior High School Students - Catador , Jose Jr. (Journal of Interdisciplinary Perspectives, 2024)
This study aims to determine the correlation and predictors of students’ performance in mathematics based on the eight domains of metacognition: declarative, procedural, conditional, planning, information management strategy, comprehension monitoring, debugging strategy, and evaluation. This study employed a descriptive-correlational research design conducted with 272 Senior High School Grade 11 students enrolled in the academic track. The research instruments utilized were the Metacognitive Awareness Inventory to assess students’ metacognitive awareness while the multiple-choice test was used to measure students’ performance in mathematics, with reliability coefficients of .853 and .790, respectively. Descriptive and inferential statistics, such as Chi-square and multiple regression analysis, were employed to interpret and analyze the data. Utilizing the descriptive statistics, results reported that metacognitive knowledge attained a mean score of 3.69 while the metacognitive control/regulation obtained a mean score of 3.65 with an overall mean score of 3.67 interpreted as aware, respectively. Furthermore, the results revealed a significant association between students’ performance in mathematics and their metacognitive awareness. The study highlighted that high-performing students in mathematics were those who effectively utilized and managed their metacognitive awareness. Moreover, it was found that greater awareness of metacognitive thinking correlated with better performance in mathematics. Additionally, the results indicated that 75.3% of metacognitive domains contributed to students’ success in mathematics. However, only declarative, procedural, conditional, and debugging strategies significantly predicted students’ success in mathematics. This suggests that students who effectively use and manage these specific metacognitive skills are more likely to excel in mathematics. In essence, this study highlights the crucial role of metacognition in mathematics learning. By fostering students’ awareness and utilization of these powerful thinking strategies, teachers can empower learners to excel in mathematics and beyond.